PENGARUH MODEL TALKING STICK TERHADAP HASIL BELAJAR IPS SISWA - Maiyona Ovartadara; Darmansyah Nabar; Yanti Fitria (STKIP Subang, 2022)
The purpose of this study is to ascertain whether or not elementary school students' social studies learning outcomes have improved. The Talking Stick model can help students develop critical thinking skills, speedy subject comprehension, active learning, and the ability to voice opinions and questions. Additionally, students' learning outcomes, particularly in social studies subjects, become optimal or improve when the Talking Stick model is used. The document study method, also known as meta-analysis, is used in this study to examine previous research's findings. Ten published journals were uncovered through a Google Scholar data search. The findings demonstrated that the Talking Stick learning model was successful in enhancing the learning outcomes of students, particularly elementary school students. When compared to conventional learning models, the Talking Stick model has produced better learning outcomes in social studies subjects. Adapting the current learning model to the circumstances and requirements of the students is another option if the Talking Stick model fails to improve student learning outcomes.